2007
DOI: 10.1063/1.2740334
|View full text |Cite
|
Sign up to set email alerts
|

Carbon loss induced by plasma beam irradiation in porous silica films

Abstract: Plasma-induced damages of porous silica films during plasma processes were investigated by using a plasma beam irradiation apparatus. We used the porous silica films incorporated with methyl groups to achieve high hydrophobicity. The carbon (methyl group) reductions in the film as an index of the level of damages induced by Ar, He, O2, H2, and N2 plasma irradiations were examined by x-ray photoelectron spectroscopy and secondary ion mass spectroscopy. The damage due to Ar and He plasma bombardment increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…H 2 also shows a lower carbon depletion compared to NH 3 and O 2 . During the reactive plasma ashes Si-C bonds are broken and volatile products such as CH 4 , CO, and CO 2 are formed, 3 which leads to the carbon depletion ͑see formed, which can be saturated, e.g., by adspecies such as atmospheric oxygen or by surface reconstruction. 15,16 After carbon is removed from the SiOCH layer a SiO 2 -like structure is remaining, which can be etched using post-ash diluted HF ͑dHF͒ chemical cleaning processes.…”
Section: Carbon Depth Profiling Using Auger Electron Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 also shows a lower carbon depletion compared to NH 3 and O 2 . During the reactive plasma ashes Si-C bonds are broken and volatile products such as CH 4 , CO, and CO 2 are formed, 3 which leads to the carbon depletion ͑see formed, which can be saturated, e.g., by adspecies such as atmospheric oxygen or by surface reconstruction. 15,16 After carbon is removed from the SiOCH layer a SiO 2 -like structure is remaining, which can be etched using post-ash diluted HF ͑dHF͒ chemical cleaning processes.…”
Section: Carbon Depth Profiling Using Auger Electron Spectroscopymentioning
confidence: 99%
“…It is reported that during plasma processes the ULK film is damaged, which is related to the carbon loss. 3 This is explained due to smaller dissociation energy for Si-C ͑ϳ447 kJ/ mol͒ compared to Si-O ͑ϳ800 kJ/ mol͒. 4 It was observed that during the carbon depletion dangling bonds occur, 5 which form new Si-O or Si-OH bonds after exposing to the atmosphere.…”
Section: Introductionmentioning
confidence: 95%
“…It may be assumed that this process has no direct influence on the change of porosity. This assumption is not in conflict with the results reported in [11,13,22]. So, following the approach described by us, we do not consider the effect of the UV radiation of plasma causing rupture of the strong Si-O-Si bonds, though we do not exclude this possibility as well.…”
Section: Molecular Structurementioning
confidence: 70%
“…21 Also the breaking of Si-CH 3 bonds by He and Ar metastable atoms has been reported. 22 We assume thus that the products which are needed to form the nanowires are released from the CuCl or CuBr matrix by the He plasma irradiation. These products can diffuse on the surface or escape to the vapor phase.…”
Section: Discussionmentioning
confidence: 99%